AB0787 Study of serum sclerostin levels in association to enthesial ultrasonography in egyptian psoriatic arthritis patients. (15th June 2017) - Elmallah, R; Attar, E EL; Farrag, D; Samaha, D; ,
Abstract : Background: Psoriatic arthritis (PsA) is characterized by focal bone erosions and new bone formation, suggesting an uncoupling of osteoblast–osteoclast homeostasis [1]. Serum sclerostin is a protein inhibitor of wnt signaling pathway of bone formation implicated in the suppression of bone repair in inflammatory arthritis. The role of sclerostin in osteoimmunology and inflammatory arthritides is still controversial [2]. Objectives: This study aimed at measuring serum sclerostin in psoriatic arthritis men and to correlate its levels with disease activity scores, ultrasonographic findings and bone mineral density in those patients Methods: This study included 30 male patients diagnosed with Psoriatic arthritis (PsA), 15 healthy age and sex matched volunteers as control group. Patients disease activity index measured. Clinical assessment by Leed's enthesitis Index (LEI) [3], Spinal manifestations scored according to Bath Ankylosing Spondylitis Activity Index [4], Serum sclerostin measured using enzyme linked immunosorbent assay. Ultrasonography of enthesis at Leeds enthesitis sites [5] and dual energy x-ray absorbiometry (DEXA) at the lumbar spine. Results: The study included 30 PsA male patients with a mean age of 43.33±8.33 mean, body mass index (BMI) of 26.87±2.63 and 15 healthy age and sex matched controls with a mean age of 42.12±7.22 mean BMI of 25.87±3.51 with an unsignificant difference between two groups. Serum sclerostin level significantly higher in PsA patients compared to controls with a mean of (0.64 and 0.37ng/ml) respectively, positive significant correlation with patients' age, disease activity scores, ultrasonographic findings of inflammation and damage at the enthesis as well as negative correlation with DEXA at lumbar spine. A positive though non-significant correlation detected between serum sclerostin and Leeds clinical enthesitis index (LEI) and CRP. Conclusions: sclerostin plays important role in pathogenesis of psoriatic arthritis and associated with bone damage either systemic or localized. Further studies for the effect of treatment on serum sclerostin, ultrasonographic and bone mineral density findings is recommended References: Homaira Rahimi & Christopher T. Ritchlin. Altered Bone Biology in Psoriatic Arthritis. Curr Rheumatol Rep (2012) 14:349–357. Matzelle MM, Gallant M, Condon KW, et al. Resolution of inflammation induces osteoblast function and regulates the Wnt signaling pathway. Arthritis Rheum 2012; 64:1540–1550. Healy PJ and Helliwell PS: "Measuring clinical enthesitis in psoriatic arthritis: assessment of existing measures anddevelopment of an instrument specific to psoriatic arthritis." Arthritis Care and Research 2008; 59(5):686–691. Garrett S, Jenkinson T, Kennedy LG et al. A new approach to defining disease status in ankylosing spondylitis: the Bath ankylosing spondylitis disease activity index. J Rheumatol (1994); 21 (12): 2286–2291. Ibrahim G, Groves C, Chandramohan M, Beltran A, Valle R, Reyes B, Healy P, Harrison A and Helliwell P S. Clinical and Ultrasound Examination of the Leeds Enthesitis Index in Psoriatic Arthritis and Rheumatoid Arthritis. ISRN Rheumatology Volume 2011(2011), Article ID 731917, http://dx.doi.org/10.5402/2011/731917. Disclosure of Interest: None declared